2018
DOI: 10.30556/jtmb.vol14.no1.2018.387
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Koagulan Hasil Percobaan Dengan Koagulan Komersial Menggunakan Metode Jar Test

Abstract: ABSTRAKPolialuminium khlorida (PAC) dan tawas merupakan koagulan yang umum digunakan pada proses pengolahan air limbah. Kedua jenis koagulan tersebut mempunyai sifat yang dapat menarik partikel-partikel lain dalam media air, sehingga berat, ukuran dan bentuknya menjadi semakin besar dan lebih mudah mengendap. PAC adalah garam khusus dari senyawa aluminium klorida yang mampu memberikan daya koagulasi dan flokulasi yang lebih kuat dibandingkan dengan garam-garam aluminium yang biasa seperti aluminium sulfat atau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Bak koagulasi berbentuk persegi yang menggunakan pengadukan cepat tipe hidrolis dengan memanfaatkan gravitasi yang terjadi pada terjunan air. Bangunan koagulasi memiliki bak pembubuh koagulan berupa aluminium sulfat Al2(SO4)3 atau tawas yang mempunyai kemampuan untuk menjernihkan air [8].…”
Section: Perencanaan Intake Ipa Dan Reservoirunclassified
“…Bak koagulasi berbentuk persegi yang menggunakan pengadukan cepat tipe hidrolis dengan memanfaatkan gravitasi yang terjadi pada terjunan air. Bangunan koagulasi memiliki bak pembubuh koagulan berupa aluminium sulfat Al2(SO4)3 atau tawas yang mempunyai kemampuan untuk menjernihkan air [8].…”
Section: Perencanaan Intake Ipa Dan Reservoirunclassified
“…On the basis of the aforementioned investigations, it has been confirmed that electrocoagulation and the combination of electrocoagulation and coagulation effectively remove pollutants from different types of water. In broad terms, the coagulation process involves the addition of chemicals to the water to be treated so that the colloidal particles are destabilized into bulky flocs and the organic matter in the liquid waste is dissolved in the floc, allowing the impurities in the water to be separated through a solidliquid filtration process [7]. According to [8], the coagulation process has the merits of being simple, affordable, capable of separating different types of particles in water, and employing materials that are abundant in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Jar test is a test method to determine the ability of a coagulant and determine the operating conditions of the optimum dosage in the WWTP. The jar test method imitates the coagulation and flocculation processes to remove suspended solids and organic matter which can cause turbidity, odor, and taste (Husaini et al, 2018). The selection of the dose that optimally remove the pollutant is determined by seeing at the final results of the TSS test, the most optimum dose is the lowest TSS level.…”
Section: Introductionmentioning
confidence: 99%